An Evaluation of the Effectiveness of the Data Protection and Privacy Act in Protecting the Right to Privacy in Uganda - Comfort Rutaya Muruhura (Uganda Christian University, 2025)
This study explores the effectiveness of the Data Protection and Data Privacy Act in protecting the right to privacy in Uganda. The right to privacy is a fundamental human right enshrined in both international human rights instruments and national constitutions. In Uganda, the enactment of the Data Protection and Privacy Act, cap 97 marked a significant step in addressing emerging privacy challenges in an increasingly digital society. With the employment of the Doctrinal research method This dissertation critically examines the effectiveness of the Data Protection and Privacy Act in safeguarding the right to privacy in Uganda, particularly in the context of rapid technological advancements, expanding digital surveillance, and data-driven governance in relation to one‟s right to privacy.The study therefore explores regional, international and national legal, institutional, and practical frameworks on data protection and data privacy for instance the General Data Protection Regulation (GDPR) and the African Union Convention on Cyber Security and Persona Data Protection (Malabo Convention) , assessing their adequacy in ensuring the protection of personal data and the enforcement of privacy rights, the rights of data subjects and the role of the different stake holders such as the Personal Data Protection Officer (PDPO). The dissertation looks into the several enforcement challenges and limitations integrated into the national, legal, institutional and policy frameworks. These challenges and limitations range from limited public awareness, weak penalties imposed by the law, inexperienced and incompetent data protection officers, political interference and lack of independence among others and how these challenges have negatively affected the enjoyment of the right to data privacy in Uganda. In conclusion the study highlights the critical need for consorted efforts in protecting and upholding the right to data privacy and protection in Uganda. It further gives several recommendations focused at integrating the legal and institutional structures for data protection that: promote public awareness by applying countrywide campaigns to enhance interpretation of data protection rights, promote accountability by strengthening implementation mechanisms to make sure data controllers and processors act in accordance with DPPA including stricter oversight and penalties, support SME compliance by providing subsidies and simplified guidelines to allow small and medium enterprises adopt stable data practices, address technological challenges by improving cyber security infrastructure and mandate secure data storage to combat breaches and unaccredited access, revise legal provisions by amending the DPPA to clarify exemptions and strengthen penalties, combat surveillance by putting in place judicial oversight for surveillance activities and whistleblower protections to escape abuse and ensure transparency and lastly provide financing for CSOs to increase advocacy by distributing resources to civil society organizations.
Undergradaute Research